2017
DOI: 10.22456/1679-9216.80582
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Morphometric Examination of the Testes of Boars and Male Pigs Immunocastrated with Improvac®

Abstract: Background: Surgical castration of male piglets is frequently performed to prevent development of an unpleasant taste and flavor in meat of mature males, called boar taint. Disadvantages of this method are primarily related to the lower feed efficiency of surgically castrated male pigs, production of less lean meat and more fat on the carcasses than boars, as well as ethical issues associated with the procedure itself. Immunocastration is a method of immunization against gonadotropinreleasing hormone (GnRH) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The injection of the vaccine is a systemic event that disturbs the hormonal homeostasis of the animal thus adverse effects could be expected in other tissues apart from the testes. A previous study has suggested that immunization against GnRH damages the hypothalamus [ 45 ]. In addition, findings from boars immunocastrated with GnRH antagonist, deslorelin, Polish Landrace × (Duroc × Pietrain) showed morphological and functional alterations in the testes and epididymis, although with a significant increase in spermatozoa production [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The injection of the vaccine is a systemic event that disturbs the hormonal homeostasis of the animal thus adverse effects could be expected in other tissues apart from the testes. A previous study has suggested that immunization against GnRH damages the hypothalamus [ 45 ]. In addition, findings from boars immunocastrated with GnRH antagonist, deslorelin, Polish Landrace × (Duroc × Pietrain) showed morphological and functional alterations in the testes and epididymis, although with a significant increase in spermatozoa production [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…PDFGFα signaling is a regulator of many developmental processes, including the formation of the male gonad [ 45 ]. PDGFRα is the only known marker of ALC stem cells that can self-renew and give rise to ALCs both in vivo and in vitro [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the timing of the two doses relative to slaughter is particularly important, as reproductive function tends to recover over time. While disrupted testis morphometry and spermatogenesis are reported in GnRH-immunized pigs at slaughter age (~6 months old) ( 497 , 508 , 509 ), boars treated with two doses of Improvest® at 10 and 15 weeks of age recovered testosterone levels by 40 weeks of age and sperm concentration and motility by 60 weeks ( 509 ). Because hogs are usually sent to market by 24–26 weeks of age, before the testis can recover, the immunization procedure is considered equivalent to castration.…”
Section: Methods Of Sterilizationmentioning
confidence: 99%
“…Puberty is a period characterized by rapid reproductive development and may be perceived by the increase in testicular growth. On the other hand, the effectiveness of immunocastration can be predicted indirectly through testicular measurements [24][25][26] or the development of sexual accessory glands [27], as immunocastrated animals have less developed genital organs [28]. The morphometric analysis of scrotal gonads, considering pre-and post-pubertal values, can then be a useful tool when evaluating the effectiveness of immunocastration protocols.…”
Section: Introductionmentioning
confidence: 99%